Interview with Tatiana A. Pokivailova. 19 October 2021. Moscow, Institute of Slavic Studies - Tatiana Pokivailova (Славянский мир в третьем тысячелетии, 2022)
At the request of the editorial board of the journal Slavic World in the Third Millennium, Tatyana Andreevna Pokivailova (born 1936), D.Sc. in History, senior researcher at the Institute of Slavic Studies of the Russian Academy of Sciences, recounts her life and career path in historical research. In 1960, she graduated from the Faculty of History of Moscow State University, and since 1968 all her professional activity has been associated with the Institute of Slavic Studies. Tatyana Andreevna is a recognised specialist in the modern history of Romania and on key issues in the history of Soviet-Romanian relations. She is the author of many dozens of papers and introduced into circulation a large number of archival documents revealing the offi cial position of Moscow towards Romania in different decades. Tatyana Andreevna spoke about her childhood and youth, student years, work with colleagues at the Institute of Slavic Studies, research trips abroad, and long-term contacts with Romanian colleagues within the framework of joint projects, as well as about the activities of the bilateral Russian-Romanian commission of historians. Her memoirs show how diffi culties in Russian-Romanian and Soviet-Romanian relations in the twentieth century affected the work of historians.